Correction: Chakraborty et al. Bromelain a Potential Bioactive Compound: A Comprehensive Overview from a Pharmacological Perspective. Life 2021, 11, 317 - Chakraborty, Arka Jyoti; Mitra, Saikat; Tallei, Trina E.; Tareq, Abu Montakim; Nainu, Firzan; Cicia, Donatella; Dhama, Kuldeep; Emran, Talha Bin; Simal-Gandara, Jesus; Capasso, Raffaele (Life (Basel, Switzerland), 2024)
The authors were not aware of errors made in one small subsection (Section 6.17. Antidiarrheal Effect, including the data in the table of effects) of this paper [...].The authors were not aware of errors made in one small subsection (Section 6.17. Antidiarrheal Effect, including the data in the table of effects) of this paper [...].